Application of Theory of Planned Behavior on COVID-19 Vaccine Uptake in Palu, Central Sulawesi, Indonesia - Gadis Nur Anggreani; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2023)
Background: According to secondary data from the Central Sulawesi Provincial Health Office, updated information regarding the COVID-19 vaccination in Palu City, Central Sulawesi has only reached 4.82%. As of Monday, March 14 2022. This data can be said to be lagging behind vaccination coverage rates because there are still many people who have not carried out vaccinations, this can be applied through Theory Planned Behavior to the use of COVID-19 vaccination at the Palu City Health Center, Central Sulawesi. Subjects and Method: Qualitative study with key informant interviews. Interviews were conducted in Palu, Central Sulawesi, Indonesia. Interviews were conducted with 7 people who had not received the COVID-19 vaccination at all, 4 people who had received the second dose of COVID-19 vaccination, 4 people who had received the third dose of COVID-19 vaccination, and key informant 1 City health center promotion worker Palu, Head of the surveillance section of the Palu City Health Service and immunization as well as the COVID-19 Task Force, as well as 1 additional informant from the family. Results: It can be seen that the lack of knowledge has a great impact on attitudes towards behavior from the community, in which in addition to believing in negative news about the COVID-19 vaccination, there is also the influence of the subjective norm variable, namely the prohibition from the family in carrying out the COVID-19 vaccination, but in the predictive variable behavioral control had little impact on the use of the COVID-19 vaccination in Palu City. Conclusion: In this study it was concluded that the application of the Theory of Planned Behavior on the use of COVID-19 vaccination in Palu City, Central Sulawesi, had an effect especially in terms of attitude towards behavior variables and subjective norm variables. Keywords: vaccination, COVID-19, theory planned behavior. Correspondence: Gadis Nur Anggreani. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: anggreanigadis@gmail.com. Mobile: +6281335205131.